Territorial structure of the denominational space of the South-East Baltic - Manakov, A. G.; Dementiev, V. S. (Baltic Region, 2019)
The South-East Baltic is a meeting place of three branches of Christianity: Orthodoxy, Catholicism, and Lutheranism. Dominant in the Baltic region, these religious confessions define the cultural landscape of the area. At the same time, they have an indirect effect on socio-economic development. In this study, we aim to identify the main components of the territorial structure and the formation and transformation factors of the denominational space in the South-East Baltic. The complexity of the denominational structure of the local population stems from the centuries-long position of this region as a political buffer zone. We calculate the potential denominational structure and the potential religious fractionalisation index at the level of basic territorial units and regions southeast of the Baltic Sea. Based on this, we identify the main components of the territorial structure of the denominational space, which includes three denominational shields and contact zones between them. From a practical viewpoint, these components suggest a new variant of the territorial differentiation of the Baltic region. This variant has only limited relevance to ethnic and socioeconomic zoning.